Disinhibitory Action of Astrocytic GABA at the Perforant Path to Dentate Gyrus Granule Neuron Synapse Reverses to Inhibitory in Alzheimer's Disease Model - Yarishkin, Oleg; Lee, Jaekwang; Jo, Seonmi; Hwang, Eun Mi; Lee, C. Justin (KOREAN SOC BRAIN & NEURAL SCIENCE, KOREAN SOC NEURODEGENERATIVE DISEASE, 2015)
Like neurons, astrocytes produce and release GABA to influence neuronal signaling. At the perforant path to dentate gyrus granule neuron synapse, GABA from astrocyte was found to be a strong inhibitory factor, which impairs synaptic transmission, synaptic plasticity and memory in Alzheimer's disease. Although astrocytic GABA is observed in many brain regions, its physiological role has not been clearly demonstrated yet. Here, we show that astrocytic GABA exerts disinhibitory action to dentate granule neurons by targeting GABA(B) receptors of GABAergic interneurons in wild-type mice. This disinhibitory effect is specific to a low intensity of electrical stimulation at perforant path fibers. Inversely in Alzheimer's disease model mice, astrocytic GABA targets GABA(A) receptors and exerts inhibitory action by reducing release probability of glutamatergic perforant path terminals. These results suggest that astrocytic GABA differentially modulates the signaling from cortical input to dentate gyrus under physiological and pathological conditions.